Accuracy of the SenseWear Armband™ during ergocycling - Brazeau, A.-S.; Karelis, A. D.; Mignault, D.; Lacroix, M.-J.; Prud'homme, D.; Rabasa-Lhoret, R. (International Journal of Sports Medicine, 2011)
The present study aims to show the accuracy of a portable motion sensor, the SenseWear Armband, for the estimation of energy expenditure vs. energy expenditure measured by indirect calorimetry during ergocycling. 31 healthy adults (52% women; age: 26.7±6.3 years; Body Mass Index: 23.9±3.3 kg/m2) completed a 45-min ergocycling session at 50% of their VO2peak. Despite a significant underestimation of 18.7±13.2 kcal during the first 10 min of the activity (T=5.06; p<0.001), we observed an overall good agreement between energy expenditure estimated by the SenseWear Armband during ergocycling and indirect calorimetry (260.3±80.1 vs. 287.8±97.1 kcal, respectively) (T=-2.148; p=0.04) and a significant intra-class correlation (r=0.81; p<0.001). The results of the present study indicate that the SenseWear Armband underestimated energy expenditure during a 45-min ergocycling session at a 50% VO2peak intensity, mainly during the first 10 min. Underestimation at the onset of the activity warrants further research.